Whole genome sequencing in ROHHAD trios proved inconclusive: what’s beyond? - Grossi, A.; Rusmini, M.; Cusano, R.; Massidda, M.; Santamaria, G.; Napoli, F.; Angelelli, A.; Fava, D.; Uva, P.; Ceccherini, I.; Maghnie, M. (Frontiers in Genetics, 2023)
Rapid-onset Obesity with Hypothalamic dysfunction, Hypoventilation and Autonomic Dysregulation (ROHHAD) is a rare, life-threatening, pediatric disorder of unknown etiology, whose diagnosis is made difficult by poor knowledge of clinical manifestation, and lack of any confirmatory tests. Children with ROHHAD usually present with rapid onset weight gain which may be followed, over months or years, by hypothalamic dysfunction, hypoventilation, autonomic dysfunction, including impaired bowel motility, and tumors of neural crest origin. Despite the lack of evidence of inheritance in ROHHAD, several studies have been conducted in recent years that have explored possible genetic origins, with unsuccessful results. In order to broaden the search for possible genetic risk factors, an attempt was made to analyse the non-coding variants in two trios (proband with parents), recruited in the Gaslini Children's Hospital in Genoa (Italy). Both patients were females, with a typical history of ROHHAD. Gene variants (single nucleotide variants, short insertions / deletions, splice variants or in tandem expansion of homopolymeric tracts) or altered genomic regions (copy number variations or structural variants) shared between the two probands were searched.Currently, we have not found any potentially pathogenic changes, consistent with the ROHHAD clinical phenotype, and involving genes, regions or pathways shared between the two trios. To definitively rule out the genetic etiology, third-generation sequencing technologies (e.g. long-reads sequencing, optical mapping) should be applied, as well as other pathways, including those associated with immunological and autoimmune disorders, should be explored, making use not only of genomics but also of differentomic datasets.